2020
DOI: 10.2147/cmar.s250867
|View full text |Cite
|
Sign up to set email alerts
|

<p>SOX10 – A Novel Marker for the Differential Diagnosis of Breast Metaplastic Squamous Cell Carcinoma</p>

Abstract: Introduction: Differential diagnosis of metaplastic squamous cell carcinoma of breast (MSCCB) is difficult. In particular, in terms of metastatic MSCCB, because of the low speciality of traditional markers such as mammaglobin, gross cystic disease fluid protein-15 (GCDFP-15) and GATA binding protein 3 (GATA3), the most common problem is differentiating the spread of MSCCB to the lung from a primary lung squamous cell carcinoma. It is urgently required to explore a novel marker to aid in differential diagnosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…2h ). Consistent with previous reports 37 , 50 , we also detected nuclear SOX10 in an independent cohort of metaplastic breast cancers (MBC; Asia-Pacific Metaplastic Breast Cancer consortium 51 ). Compared to cross-sectional cases, SOX10 staining was more heterogeneous in MBCs, and was not associated with TN status (Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…2h ). Consistent with previous reports 37 , 50 , we also detected nuclear SOX10 in an independent cohort of metaplastic breast cancers (MBC; Asia-Pacific Metaplastic Breast Cancer consortium 51 ). Compared to cross-sectional cases, SOX10 staining was more heterogeneous in MBCs, and was not associated with TN status (Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with previous reports 37,50 , we also detected nuclear SOX10 in an independent cohort of metaplastic breast cancers (MBC; from the Asia-Pacific Metaplastic Breast Cancer consortium 51 ). Compared to cross-sectional cases, SOX10 staining was more heterogeneous in the MBC cohort and was not associated with TN status (Fig- S2j); but was prognostic in MBCs with a TN phenotype (Fig- 2g).…”
Section: Sox10 Is Associated With Poor Clinical Outcomes In Tnbcsupporting
confidence: 92%
“…The goal of this study is to emphasize that SOX10 is consistently positive in TNBC with increasing grade of tumor and in diagnosing unknown primary; hence, it can be helpful for pathologists to avoid misleading diagnoses at metastatic sites. SOX10 expression may lead to confusion in diagnosis but many studies have proven that breast carcinomas, particularly basal-like, triple-negative phenotypes, are also labeled by SOX10 [19]. This study is the continuation of a similar study conducted by Katharina et al in Germany [20].…”
Section: Discussionmentioning
confidence: 53%
“…A similar study conducted in China by Linfang et al showed concordant results [18]. Hence, SOX10 has promising utility in the diagnosis and can help in molecular classification [19]. However, when we encounter triple-negative breast cancer, particularly at metastatic sites, it is challenging to diagnose even with a particular clinical presentation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation